2006
DOI: 10.1016/j.sna.2006.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Micro-hotplates on polyimide for sensors and actuators

Abstract: In this communication, we present the fabrication and the characterisation of micro-heating elements made on polyimide (PI) sheets and on spin coated polyimide membranes. Different types of polyimide and heater materials were investigated to realise micro-hotplates for gas-sensing and thermal actuating applications. The effects of the type of polyimide used and of the different annealing performed on the mechanical and electrical properties of the metallic heaters were characterised. Using an optimised combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…As a result, microsensor arrays obtained using such microhotplate design will undoubtedly suffer from a very low sensor density. Briand et al [17] have reported to make microhotplate gas sensor on a polyimide layer (as insulating layer) to avoid tedious front micromachining involved in processing air pit microhotplate gas sensors. However, they end up with a hotplate size of 1.5 mm wide and power consumption of 66 mW to reach the temperature of 325 • C. Therefore, we are in urgent need of area efficient gaseous sensor design with low power consumption to present a cost-effective manufacturing of sensor arrays on the wafer.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, microsensor arrays obtained using such microhotplate design will undoubtedly suffer from a very low sensor density. Briand et al [17] have reported to make microhotplate gas sensor on a polyimide layer (as insulating layer) to avoid tedious front micromachining involved in processing air pit microhotplate gas sensors. However, they end up with a hotplate size of 1.5 mm wide and power consumption of 66 mW to reach the temperature of 325 • C. Therefore, we are in urgent need of area efficient gaseous sensor design with low power consumption to present a cost-effective manufacturing of sensor arrays on the wafer.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the work we have recently reported on the development of micro-heating elements on polyimide (PI) for sensors and actuators [5], we detail here the application of polymeric hotplates for the realisation of low-power metal-oxide gas sensors. Specific fabrication processes are evaluated for the integration of metal-oxide gas sensors on two types of PI hotplates, made on PI sheets and on silicon substrates.…”
Section: E-mail Address: Danickbriand@uninech (D Briand)mentioning
confidence: 99%
“…The polyimide micro-hotplates on Upilex and on silicon withstood an annealing in air at a maximum temperature of 450 • C, the membrane from the silicon device exhibited a significant membrane deformation compared to the Upilex device [5]. Therefore, these polymeric gas-sensing platforms were drop coated with SnO 2 and annealed in air at 450 • C. The MOX gas sensors realised on the two types of polyimide micro-hotplates are presented in Figs.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) Platinum is selected as the sensor sensitive material, as it has a good thermal response that corresponds linearly to temperature. (13)(14)(15) There is much interest in the development of polyimide-based devices for medical applications, which include implantable microelectrodes (16) for neural prostheses, (17) micro-hotplates and microheater arrays, (18,19) and bolometers. (20) To our knowledge, no one has addressed the fabrication of a temperature microsensor to measure the temperature distribution on the skin during ultrasound exposure.…”
Section: Introductionmentioning
confidence: 99%